Pelatihan Pembuatan Silase Limbah Sayuran Pasar untuk Pakan Ayam - Umbang Arif Rokhayati (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
The main problem faced by Sumber Rejeki chicken farmers is the provision of feed that meets nutritional needs, but is affordable. On the other hand, the people of Hulawa Village are faced with the problem of the large amount of low grade vegetable waste and vegetable parts that cannot be consumed by humans. Vegetable waste that accumulates and rots, can cause environmental pollution and strong odors in landfills. Therefore, as an alternative to reduce the potential for pollution as well as establishing mutually beneficial cooperation in problem solving, it is necessary to utilize vegetable waste into raw materials for chicken feed. This community training activity aims to inform and practice directly in processing market vegetable waste into chicken feed. Counseling and direct practice of making feed, assistance during training, and observation of the results of activities. Three types of vegetable waste with the highest amount used as raw material for pellets are cabbage, white cabbage leaves, and mustard greens. The results of the activity showed that there was an increase in knowledge and skills in the utilization of vegetable waste into chicken feed.